Determining the role of basophil activation testing in reported type 1 allergy to beta-lactam antibiotics - Reitmajer, Markus; Strauss, Antonia; Klinger, Christian; Maaß, Maximiliane; Kempf, Wolfgang E.; Fischer, Joerg; Kneilling, Manfred; Volc, Sebastian (Frontiers in Allergy, 2024)
BackgroundAllergy to beta-lactam antibiotics (BLA), especially to penicillin, is the most commonly reported drug allergy by patients. Alternative antibiotics can yield negative consequences, such as extended hospitalization days due to less efficacy and overall higher costs. The basophil activation test (BAT) is an in vitro assay, in which activation of an individual's own basophils is quantified by flow cytometry. It is an increasingly applied in vitro method in allergy testing that is also gaining traction in drug allergies.MethodsWe correlated 37 BAT results with skin test results. The cohort exclusively included patients with suspected type I BLA allergy. In addition, we examined the concordance of these results with clinical symptoms reported in the BLA patients’ medical histories.ResultsBLA-BAT revealed a high specificity of 92.3% [95% confidence interval (CI) 66.7–98.6] but a low sensitivity of only 20.8% (95% CI 9.24–40.47) using BLA-skin tests as a comparator. Negative BLA-BAT in patients with a history of grade I anaphylaxis yielded doubt on the assumption of grading. The exclusion of grade I BLA anaphylaxis increased the sensitivity to 29.4% (95% CI 13.28–53.13) with a still high specificity of 85.7% (95% CI 48.69–97.43). When ImmunoCAP was available, we compared specific IgE and BAT results by using Cohens' kappa (κ) and revealed a moderate level of agreement (κ = 0.538, p = 0.029).ConclusionBAT reveals specific positive results exclusively in patients with cephalosporin anaphylaxis. However, these findings could not be generally confirmed in the heterogeneous group of BLA.